Joint channel estimation and ICI cancellation algorithm for pilot-assisted OFDM systems - JIANG Qi 1; ZHAO Chun-ming 1; JIA Peng 1 (Tongxin xuebao)
The inter-carrier interference caused by double-selective channels in OFDM systems was analyzed.An OFDM channel estimation method with new pilot structure was also proposed,based on which the channel estimation in time domain and the ICI cancellation could be done within one OFDM symbol.The simulation results show that the proposed joint channel estimation and ICI cancellation algorithm can provide more accurate channel information,and improve system performance apparently.